Research on Modeling of Speech Recognition Based on Deep Learning - Zhang, Min (Journal of Theory and Practice of Management Science, 2025)
With the development of technology, the application of speech recognition is becoming increasingly widespread, and intelligent speech recognition has great significance. The article introduces the working mechanism and classification of speech recognition systems, and designs the system development environment and framework. Design the collection of speech datasets, preprocessing of speech data, feature extraction of speech data, construction of acoustic models, and construction of language models for deep learning based Chinese speech recognition. This study is capable of self recording speech or uploading speech to a server for Chinese recognition, and supports the function of translating recognized Chinese into English. This study can lay the foundation for further in-depth research on speech recognition.